Ways of forming the reading interests of younger students - Компаній, О. В. (Pedagogy of Higher and Secondary Education, 2012)
Kompaniy O. V. Ways of forming the reading interests of younger students. The author investigates the definition of theoretical knowledge, defines the abilities, characterizes exercises and stages, which promote the awakening of readers’ interests.